1999
DOI: 10.1007/s002130050817
|View full text |Cite
|
Sign up to set email alerts
|

Increased sensitivity to the locomotor depressant effect of a dopamine receptor antagonist during cocaine withdrawal in the rat

Abstract: The effect of a dopamine receptor antagonist on locomotor activity was examined during withdrawal from either self-administered or experimenter-administered cocaine. In the self-administration experiment, the locomotor response to a challenge injection of cis-flupenthixol was assessed in photocell cages at 4 h after the cessation of a 12-h cocaine self-administration session. Rats which had self-administered cocaine, and were challenged with cis-flupenthixol (0.05 mg/kg), were found to be hypoactive relative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…1, after 46 h of deprivation from a sweet-fat chow, rats that previously had 2 h access showed fewer instances of cage-crossing compared with ad libitum fed controls (standard rodent chow or high-fat, sweet rodent chow). Hypoactivity has been noted during cocaine withdrawal in rodents [41]. However, no signs of opiate-like withdrawal were noted in the other tests performed on this group, such as the somatic measures of withdrawal.…”
Section: Discussionmentioning
confidence: 75%
“…1, after 46 h of deprivation from a sweet-fat chow, rats that previously had 2 h access showed fewer instances of cage-crossing compared with ad libitum fed controls (standard rodent chow or high-fat, sweet rodent chow). Hypoactivity has been noted during cocaine withdrawal in rodents [41]. However, no signs of opiate-like withdrawal were noted in the other tests performed on this group, such as the somatic measures of withdrawal.…”
Section: Discussionmentioning
confidence: 75%
“…Decreased dopaminergic function achieved through post-synaptic receptor blockade has long been associated not only with deficits in cocaine reward but also with deficits in motoric capacity (Ahlenius et al, 1987; Baldo et al, 1999; Chan and Webster, 1971; Delfs et al, 1990). Indeed, several investigators have suggested that a drug’s capacity to enhance locomotor activity serves as a predictor of, or is associated with, the reinforcing actions of the drug (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, withdrawal from cocaine is associated with increased anxiety-like behavior in the elevated plus maze [22, 23]. Cocaine withdrawal, however, also suppresses locomotor activity [24, 25], which may yield a false-positive result in the light-dark box test. Therefore, locomotor activity was also assessed during the time spent in the dark compartment in the present study.…”
Section: Introductionmentioning
confidence: 99%